TGF-β2 downregulates osteogenesis under inflammatory conditions in dental follicle stem cells. Issue 3 (September 2018) - Um, Soyoun; Lee, Joo-Hee; Seo, Byoung-Moo
Abstract Bone formation is important for the reconstruction of bone-related structures in areas that have been damaged by inflammation. Inflammatory conditions such as those that occur in patients with rheumatoid arthritis, cystic fibrosis, and periodontitis have been shown to inhibit osteoblastic differentiation. This study focussed on dental follicle stem cells (DFSCs), which are found in developing tooth germ and participate in the reconstruction of alveolar bone and periodontal tissue in periodontal disease. After bacterial infection of inflamed dental tissue, the destruction of bone was observed. Currently, little is known about the relationship between the inflammatory environment and bone formation. Osteogenic differentiation of inflamed DFSCs resulted in decreased alkaline phosphatase (ALP) activity and alizarin red S staining compared to normal DFSCs. Additionally, in vivo transplantation of inflamed and normal DFSCs demonstrated severe impairment of osteogenesis by inflamed DFSCs. Protein profile analysis via liquid chromatography coupled with tandem mass spectrometry was performed to analyse the differences in protein expression in inflamed and normal tissue. Comparison of inflamed and normal DFSCs showed significant changes in the level of expression of transforming growth factor (TGF)-β2.Porphyromonas gingivalis (P.g .)-derived lipopolysaccharide (LPS) was used to create in vitro inflammatory conditions similar to periodontitis. The osteogenic differentiation of LPS-treated DFSCs was suppressed, and the cells displayed low levels of TGF-β1 and high levels of TGF-β2. DFSCs treated with TGF-β2 inhibitors showed significant increases in alizarin red S staining and ALP activity. TGF-β1 expression was also increased after inhibition of TGF-β2. By examining inflamed DFSCs and LPS-triggered DFSCs, these studies showed both clinically and experimentally that the increase in TGF-β2 levels that occurs under inflammatory conditions inhibits bone formation. Osteogenesis: Transforming growth factor-β2 inhibits bone formation during inflammation During inflammation, increased transforming growth factor (TGF)-β2 inhibits bone formation in dental follicle stem cells (DFSCs). Hitherto, the relationship between inflammation and bone formation has been poorly understood. But a team headed by Byoung-Moo Seo of Seoul National University, Republic of Korea examined the different functions of two types of TGF-β (a protein that is a key regulator of bone formation): TGF-β1 and TGF-β2. By means of cell cultures and in vivo experiments in mice, the team conducted its investigation on DFSCs: stem cells (non-specialised cells) in the dental follicle, which surrounds a tooth before it erupts. The authors found that inflammation led to an increase in TGF-β2, and that increase inhibited bone formation. The results of the study have implications for the future therapeutic application of DFSCs in bone-loss diseases.